Epidemiología molecular de la candidiasis vulvovaginal (CVV) en gestantes en Argentina - Mucci, María Josefina (2015)
Introduction. Pregnancy is one of the risk factors for the development of vulvovaginal\ncandidiasis (VVC). Its diagnosis and treatment can prevent potential obstetrical and gynecological\ncomplications. The species Candida albicans is the primary etiological agent; however, VVC due\nto non-Candida albicans species has increased gradually and is becoming more resistant to\nantifungal agents. Thus, the identification of Candida isolates is essential since conventional\nmethods in diagnostic microbiology are inconclusive for some species.\nObjective. Report on the frequency of VVC and the carriage of Candida species in\nimmunocompetent pregnant patients. Determine the distribution and prevalence of yeasts from\ndifferent species isolated from patients with VVC and asymptomatic carriage of these\nmicroorganisms. Differentiate the C. albicans species complex (C. albicans, C. dubliniensis and C.\nafricana), C. parapsilosis and C. glabrata by molecular methods. Compare conventional\nmicrobiological techniques with molecular methods aimed at its detection. Determine the\nfrequency of other pathogens with increased obstetric risk factors or causing vulovaginal\ninfections and recognize the possible association with the different Candida species.\nMaterials and Methods. We obtained 210 vaginal swabs and 64 vaginal secretion\nsamples from immunocompetent pregnant women at 35-37 weeks of gestation to analyze\nStreptococcus agalactiae and its association with Candida species. For yeast identification,\nconventional microbiological studies were performed (microscopic examination of samples,\nCHROMagar Candida culture media, chlamydoconidia production in milk agar 1% Tween 80 and\nStaib medium, assimilation of sugars, and API ID 32C method) and molecular methods (PCR from\nyeast suspensions using specific primers in order to: i) differentiate between C. albicans, C.\ndubliniensis and C. africana (actin and HWP1 gene); ii) C. parapsilosis, C. orthopsilosis and C.\nmetapsilosis (ITS1-ITS2 regions of the rDNA); and iii) C. glabrata, C. bracarensis and C.\nnivariensis (RLP31 gene encoding a 60S ribosomal protein). Microbiological studies were also\ncarried out by conventional methods for the identification of S. agalactiae, Ureaplasma spp.,\nMycoplasma hominis, Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomonas vaginalis.\nStatistical analysis of the results was performed using descriptive statistics and chi-square test;\nGraphPad Prism (version 6.0).\nResults: The prevalence of VVC in pregnant women was 25% (52/210). Increased\nsymptoms were observed as gestation progressed, being higher in the 2nd and 3rd trimester of\npregnancy, probably secondary to the increased colonization by Candida spp. Colonization by\nCandida spp in asymptomatic patients was 13.8%. C. albicans was isolated in 80.7% of VVC\npatients and the remaining 19.3% showed other yeast species, whereas in 50% of asymptomatic\npatients, S. cerevisiae, Rhodotorula spp and non-Candida albicans were isolated (p <0.005). This\nsuggests that yeast colonization in the vagina is associated with non-Candida albicans or other\nyeasts and that the development of VVC could depend, among other factors, on the replacement\nof these species with C. albicans. In the VVC population, the most predominant isolates of non-\nCandida albicans species were C.glabrata (7.68%) and C. dubliniensis (3.84%). The latter two\nspecies were found in pregnant women as well as in colonizing VVC biota, in both cases with no\nsignificant differences.\nThe molecular methods used in this study allowed the differentiation of Candida species not\ndistinguished by conventional phenotyping, like C. parapsilosis sensu stricto. PCR amplification of\nthe intron of the actin gene in C. dubliniensis confirmed the conventional microbiological\nidentification. Neither the presence of C. africana, C. bracarensis nor C. nivariensis could be\nobserved by PCR using specific primers. PCR amplification of the HWP1 gene allowed the\nidentification of isolates of heterozygous and homozygous C. albicans for this gene. No significant\ndifferences were observed in VVC patients or in those with asymptomatic carriage of the\npathogen.\nWhen considering other pathogens engaged in the study population (n=210), we observed that BV\ninvolved 18.09%, C. trachomatis 1.43%, N. gonorrhoeae 0.48%, Ureaplasma spp. and\nMycoplasma hominis 17.62% and 2.85% respectively.\nS. agalactiae was found in 12.5% of pregnant women at 35-37 weeks of gestation (n=64), and\n4.7% was associated with C. albicans.\nSome Candida species were associated with bacterial vaginosis (BV), Streptococcus agalactiae,\nUreaplasma spp. and Mycoplasma hominis.\nConclusions: The prevalence of VVC in pregnant women was 25% with C. albicans being\nthe most common species. The phenotypic methods were inconclusive in identifying the different\nCandida species, while the use of molecular techniques provided a more accurate knowledge of\nthis epidemiology in pregnant women in Argentina, particularly due to the importance of C.\nalbicans and non-C. albicans species.